Nutrition students and mathematics: Competent but not confident - Clark, Karin; Cooke, Audrey; James, Anthony; Halse, Rhiannon (Anzame, 2020)
Aim: To assess skills, competence and disposition of nutrition students towards mathematics. Methods: A cross-sectional study was conducted at Curtin University, Perth, Western Australia, to assess the numeracy of undergraduate nutrition students enrolled in a level 2 biochemistry unit (n = 40). Primary outcome measures were evaluations of competence when answering discipline-specific questions and students’ confidence and perceived ease and disposition towards mathematics. Results: The majority of students were competent (mean diagnostic test score = 72%), with only four students scoring below the competence midpoint. However, many students reported low confidence and a high perception of difficulty, indicated by the majority of scores above the line of equality in self-confidence and ease of questions. Furthermore, 30% of students identified as having anxiety related to mathematical understanding and mathematical knowledge below the midpoint. Conclusions: Results showed a significant proportion of students were not confident with mathematics, despite being competent. Anxiety concerning knowledge and understanding was present in 30% of students. These findings are important for tailoring a numeracy support framework that specifically addresses confidence and disposition towards mathematics to ensure that students can succeed in the mathematical challenges inherent to their course and future nutrition career.